2011
DOI: 10.1017/s0022149x11000459
|View full text |Cite
|
Sign up to set email alerts
|

Schistosoma haematobium infections in preschool children from two rural communities in Ijebu East, south-western Nigeria

Abstract: There is an urgent need for information on schistosomiasis in preschool children, who are often excluded in mass treatment programmes. The prevalence and intensity of Schistosoma haematobium infection were determined in preschool children aged ≤ 6 years in two rural communities in Ijebu East, south-western Nigeria. Two urine samples each were collected from 83 preschool children from the two communities, tested for microhaematuria using reagent strips and then processed and examined with a microscope for S. ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 27 publications
0
21
1
Order By: Relevance
“…Many epidemiological studies emanating from this region over the years have consistently revealed a high prevalence of urinary schistosomiasis [14,30,15]. Some of these reports show that the community members are aware that their constant continuous contact with endemic water from the river is responsible for their high infection rates, but because there is no alternative water source they have no choice but to continue to depend on the contaminated water for their daily domestic activities [31].…”
Section: Discussionmentioning
confidence: 99%
“…Many epidemiological studies emanating from this region over the years have consistently revealed a high prevalence of urinary schistosomiasis [14,30,15]. Some of these reports show that the community members are aware that their constant continuous contact with endemic water from the river is responsible for their high infection rates, but because there is no alternative water source they have no choice but to continue to depend on the contaminated water for their daily domestic activities [31].…”
Section: Discussionmentioning
confidence: 99%
“…Community members of the selected area were sensitized about the research through the assistance of Primary Health Care (PHC) centre staffs and the Community Development Association (CDA) leaders. A total sampling of households within the community was done and consenting parents with children belonging to age category 0–6 years were recruited into the study in accordance with Ekpo et al [ 16 ]. Parents of children who could provide adequate stool specimen at the point of visit were asked to converge at the PHC centre where detailed anthropometric measurements of their children and interviews were made.…”
Section: Methodsmentioning
confidence: 99%
“…In the liver, they mature into adult worms and copulate [18]. After copulation females then deposit eggs into the vesicular and pelvis venous plexus of bladder [19]. The eggs then move to lumen of bladder and ureters where they are eliminated with urine [20].…”
Section: Introductionmentioning
confidence: 99%